Anti-biofilm activity of Pseudoalteromonas haloplanktis TAC125 against Staphylococcus epidermidis biofilm: Evidence of a signal molecule involvement? - PARRILLI, ERMENEGILDA; Papa, R; CARILLO, SARA; Tilotta, M; CASILLO, ANGELA; Sannino, F; Cellini, A; Artini, M; Selan, L; CORSARO, MARIA MICHELA; TUTINO, MARIA LUISA (International Journal of Immunopathology and Pharmacology, 2015)
Staphylococcus epidermidis is recognized as cause of biofilm-associated infections and interest in the development of new approaches for S. epidermidis biofilm treatment has increased. In a previous paper we reported that the supernatant of Antarctic bacterium Pseudoalteromonas haloplanktis TAC125 presents an anti-biofilm activity against S. epidermidis and preliminary physico-chemical characterization of the supernatant suggested that this activity is due to a polysaccharide. In this work we further investigated the chemical nature of the anti-biofilm P. haloplanktis TAC125 molecule. The production of the molecule was evaluated in different conditions, and reported data demonstrated that it is produced in all P. haloplanktis TAC125 biofilm growth stages, also in minimal medium and at different temperatures. By using a surface coating assay, the surfactant nature of the anti-biofilm compound was excluded. Moreover, a purification procedure was set up and the analysis of an enriched fraction demonstrated that the anti-biofilm activity is not due to a polysaccharide molecule but that it is due to small hydrophobic molecules that likely work as signal. The enriched fraction was also used to evaluate the effect on S. epidermidis biofilm formation in dynamic condition by BioFlux system.